Tingkat Pendidikan dan Literasi Keuangan Terhadap Pengelolaan Keuangan Pemilik UMKM Pasar Raya Kota Padang - Revinda, Fitria; Cerya, Efni (Politeknik Piksi Ganesha Indonesia, 2025)
This research examines the effect of educational level and financial literacy on the financial management practices of MSME owners in Pasar Raya, Padang City. Using a causal quantitative approach, the study involved 4,320 MSMEs with 100 respondents selected through proportional random sampling. Primary data were obtained via structured questionnaires and analyzed using multiple linear regression, along with classical assumption tests, F-tests, t-tests, and the coefficient of determination. The results indicate that, jointly, education and financial literacy significantly influence financial management. However, individually, education shows no significant effect, while financial literacy has a positive and significant impact. These findings highlight the importance of improving financial literacy through training and mentoring to help MSME owners manage finances effectively and maintain business sustainability.